Making climate-smart cocoa inclusive: towards a framework for gender transformation - Torvikey, G.D.; Dalaa, M.A.; Adomaa, F.O.; Abdul-Razak, S.; Amoah, I.A.; Kofituo, R.K.; Tettey, A.; Asare, R. (Informa UK Limited, 2024)
Climate-Smart Cocoa (CSC), a strategic offshoot of the wider Climate-Smart Agriculture, is gaining ground in Ghana, a cocoa export-dependent country. CSC is imperative, given the rapidly declining forests, prolonged periods of drought, pest and disease infestations, and fluctuating cocoa yields attributed to climate variability and change. Although many interventions are instituted to restore sustainable cocoa production, they are largely technicist because they do not pay attention to gender relations of production in the communities. Given the context of the embeddedness of gender inequality in access to resources, we used some CSC interventions in Ghana to reflect on the lingering questions of CSC production practices. We relied on CSC project documents, extant literature, farmer surveys and qualitative data to highlight the need for climate-smart agricultural approaches to be sensitive to structural and systemic issues that exclude female farmers. We argue that transforming norms that perpetuate unequal access to land, labour, input and extension services between men and women should be central to approaches that aim to promote sustainable and ecologically sound agricultural practices in cocoa production systems.